Stability and electronic properties of 3D covalent organic frameworks - Lukose, Binit; Kuc, Agnieszka; Heine, Thomas (Journal of Molecular Modeling, 2013)
Covalent organic frameworks (COFs) are a class of covalently linked crystalline nanoporous materials, versatile for nanoelectronic and storage applications. 3D COFs, in particular, have very large pores and low mass densities. Extensive theoretical studies of their energetic and mechanical stability, as well as their electronic properties, have been carried out for all known 3D COFs. COFs are energetically stable and their bulk modulus ranges from 3 to 20 GPa. Electronically, all COFs are semiconductors with band gaps corresponding to the HOMO-LUMO gaps of the building units. © Springer-Verlag Berlin Heidelberg 2012.
CRIS-Team Scopus Importer:2023-03-20
Keywords: Band gap; Bulk modulus; Covalent organic frameworks; Density functional tight-binding; HOMO-LUMO gap